Relationship between service quality and customer satisfaction : an empirical study of Islamic Banks in Malaysia - Abdul Razak, Dzuljastri; Zakariah, Fodol Mohamed; Jama, Ahmed Abdilahi; Burhan, Ali Ahmad (2018)
Service quality is an important and effective tool for banks to achieve customer satisfaction and earn their loyalty, especially under intense competition. Indeed, there is an strong competition between Islamic banks in Malaysia whereby each practitioner is working hard to satisfy their customers’ need for service excellence. There are few studies that have included Shariah compliance with five other variables namely tangible, reliability, responsiveness, assurance and empathy known as CARTER model. However, majority of these studies are not conducted in Malaysia and the sample size was small. There was only one study conducted in Malaysia using descriptive statistics. Hence, this study addresses this gap by conducting the survey in Klang valley region which include Kuala Lumpur, Gombak and Shah Alam.The method was carried out by survey of 300 respondents. Data is analyzed using factor analysis and multiple regressions to measure the relationship between the variables. The results indicated that compliance, reliability, and empathy have positive relationships with customer satisfaction. While the relationships with assurance, tangibles, and responsiveness are insignificant. Hence, practitioners can emphasize on the three significant factors in improving service quality. The academician can benefit by conducting more research into this body of knowledge.